VD_FINDINFO Jug / 2011 / 249 vom 14. Juli 2011 - VD Tribunal cantonal (2011)
RÉCUSATION, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE | 26 al. 1 LCR, 34 al. 1 LCR, 7 al. 3 OCR, 398 al. 4 CPP (CH)